Perceptions of the Society towards the Profile of Teachers’ Preparation Program - Praptining Rahayu; Agnita Siska Pramasdyahsari; Nurina Happy; Wawan Kurniawan; Andi Priyolistiyanto (International Journal of Research in Education, 2022)
The quality improvement of the university becomes one of the considerations in choosing the study program. Therefore, higher education branding is essential to maintain its existence in society.   As a part of the Teacher Preparation Program in Central Java, FPMIPATI UPGRIS needs a branding effort to increase its existence in the community so that it can increase the interest of prospective new students to choose it as a destination for undergraduate education. This study aims to determine public perceptions about the profile of FPMIPATI UPGRIS. The method used in this study is a cross-sectional quantitative survey method. The results showed that the profile of each Study Program at FPMIPATI consists of (1) excellent curriculum and competencies, (2) partnerships that exist in the study program, (3) Facilities, (4) programs to facilitate students to obtain funding other than scholarships, (4) profiles of graduates from each Study Program, able to be an attraction for the public, especially prospective new students.